The Correlation between Serum Inositol 1,4,5 Triphosphate Level and Primary Hypothyroidism - Matshar, Akram Sabah; Majeed, Maysaa Jalal; Mohson, Mohamed Sadoon (AL-Kindy College Medical Journal, 2022)
Background: Most primary hypothyroidism patients also experience inefficiency and irregularity. It is possible to understand the significance of myo-inositol in treating the thyroid gland by relating it to the synthesis of thyroid hormones. Study aimed to estimate serum of inositol 1,4,5-triphosphate (IP3) in primary hypothyroidism disorder and through that level it can shed light on whether it is accused of inactivity of the thyroid gland and at the same time open the doors for the use as a treatment.Subject and Methods: The study was taken from the analytical cross-sectional design.120 subjects were divided into three groups, the first group included 40 healthy subjects, the second group included 25 patients with subclinical hypothyroidism, and the last group had 55 patients with primary hypothyroidism. with the subjects chosen from a teaching laboratory in the medical city. thyroid hormones and serum TSH was determined using Enzyme Immunoassay by Tosoh instrument assay, while serum inositol 1,4,5-triphosphate (IP3) using (ELISA) system.Results: primary hypothyroidism patients showed a significant (p≤0.05) decrease level of serum IP3 when compared with healthy subjects. There is significant positive correlation with serum inositol 1,4,5 triphosphate (IP3) and each triiodothyronine S.T3 (r = 0.581, p ≤0.05), thyroxine S.T4 (r = 0.597, p ≤0.05), and significant negative correlation thyroid-stimulating hormone S.TSH (r=-0.820, p≤0.05), in primary hypothyroidism Patients.Conclusions: inositol 1,4,5 triphosphate (IP3) deficiency in primary hypothyroidism disorder may be a cause of it happening, at the same time may be useful in its treatment even if it was not studied adequately in the study, but through its effect on a thyroid hormone.